Study of kesterite CZTS thin films deposited by spin coating technique for photovoltaic applications. (March 2019) - Ziti, Ahmed; Hartiti, Bouchaib; Labrim, Hicham; Fadili, Salah; Ridah, Abderraouf; Belhorma, Bouchra; Tahri, Mounia; Thevenin, Philippe
Abstract: In this work, we study the effect of annealing temperature on structural, optical and electrical properties of Cu2 ZnSnS4 synthetized by sol gel method and deposited by spin coating technique. The samples were annealed in air at 300 °C, 325 °C and 350 °C during 10 min. The X-ray diffraction and Raman spectroscopy exhibit the formation of pure kesterite structure of CZTS. The optical parameters have been calculated from the transmittance and absorbance data giving by UV–Visible spectrophotometer in the range between 350 and 1000 nm. The band gap energy increased from 1.5 to 1.63 eV, in addition to a better electrical resistivity in the range of 0.1–0.15 (Ω cm) was found by four point probe method. A small band gap energy and best resistivity make our deposited films a suitable material as an absorber layer in photovoltaic solar cells. Highlights: Elaboration of CZTS thin films by sol gel method associated to spin coating technique. Study the effect of annealing temperature in air on structural, optical and electrical of CZTS thin films. X-ray diffraction and Raman spectroscopy show the formation of kesterite structure of CZTS thin films. The optical and electrical properties show that the CZTS absorber layers can be favorable for photovoltaic applications.